Improving the Quality and Added Value of Miana Leaves (Coleus scutellarioides) through Harvest and Postharvest Assistance at BUMDes Tanjung Asri, Mojokerto - Kartini, Kartini; Setyaningrum, Idfi; Hidayat, Ramdan; Pudjibudojo, Jatie Kusmiati Kusna (Society : Jurnal Pengabdian Masyarakat, 2026)
Miana leaves (Coleus scutellarioides) have significant potential as raw materials for herbal products due to their bioactive compounds; however, their quality is highly influenced by harvesting and postharvest handling practices. At BUMDes Tanjung Asri, the existing practices were still simple and not standardized, resulting in inconsistent quality and low added value. This community service program aimed to improve the quality and value addition of miana leaves through assistance in proper harvesting and postharvest handling. The program was implemented using a participatory approach involving four stages: development of standard operating procedures (SOPs), dissemination of SOPs, hands-on field practice, and post-training assistance. The developed SOPs covered harvesting criteria, postharvest handling, and storage processes and were presented in an infographic format. The results showed that partners were able to apply the SOPs more systematically, particularly in sorting, washing, and drying processes, leading to improved handling practices. The learning-by-doing approach effectively enhanced partners’ technical skills, while post-training assistance ensured the sustainability of SOP implementation. Overall, this program contributed to improving the quality, consistency, and added value of miana leaves at BUMDes Tanjung Asri.